2007
DOI: 10.1007/s00572-007-0122-9
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous systemin has a contrasting effect on disease resistance in mycorrhizal tomato (Solanum lycopersicum) plants infected with necrotrophic or hemibiotrophic pathogens

Abstract: A study was performed to determine the effect of the systemin polypeptide on the bio-protective effect of arbuscular mycorrhizal fungi (AMF) in tomato plants infected with Alternaria solani, Phytophthora infestans or P. parasitica. Before infection, tomato plants were colonized with two different AMF, Glomus fasciculatum or G. clarum. In addition, a group of inoculated plants was treated with systemin, just after emergence. The exogenous application of systemin marginally suppressed the resistance against A. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 61 publications
2
18
0
1
Order By: Relevance
“…However, pathogens with a necrotrophic lifestyle are hampered in their proliferation, and symptom development is less severe on mycorrhizal plants. Examples are the fungi Alternaria solani in tomato (Fritz et al, 2006;de la Noval et al, 2007), Magnaporthe grisea in rice (Campos-Soriano et al, 2012), and Botrytis cinerea in roses and tomato (Møller et al, 2009;Pozo et al, 2010).…”
Section: Mycorrhiza Effects On Above-ground Interactionsmentioning
confidence: 99%
“…However, pathogens with a necrotrophic lifestyle are hampered in their proliferation, and symptom development is less severe on mycorrhizal plants. Examples are the fungi Alternaria solani in tomato (Fritz et al, 2006;de la Noval et al, 2007), Magnaporthe grisea in rice (Campos-Soriano et al, 2012), and Botrytis cinerea in roses and tomato (Møller et al, 2009;Pozo et al, 2010).…”
Section: Mycorrhiza Effects On Above-ground Interactionsmentioning
confidence: 99%
“…Finally, several studies have observed a positive effect of the symbiosis on plant resistance to other shoot pathogens. In tomato, AM reduced disease symptoms caused by a phytoplasma and conferred protection against the necrotrophic fungus Alternaria solani (Lingua et al 2002 ;Fritz et al 2006 ;de la Noval et al 2007) . Similarly, colonisation by Glomus mosseae reduces disease symptoms and proliferation of Pseudomonas syringae in tomato leaves (J. García-Andrade and M.J. Pozo, unpublished results).…”
Section: Mycorrhiza-induced Resistance Against Pathogensmentioning
confidence: 99%
“…N0P0, tanpa inokulasi CMA dan tanpa pemupukan N, P, dan K; N0P1, diinokulasi CMA dan tanpa pemupukan N, P, dan K; N0P2, diaplikasi fungisida kimia dan tanpa pemupukan N, P, dan K; N1P0, tanpa inokulasi CMA dan dengan pemupukan N, P, dan K; N1P1, diinokulasi CMA dan dengan pemupukan N, P, dan K; N1P2, diaplikasi fungisida kimia dan dengan pemupukan N, P, dan K. kembangan penyakit yang lebih rendah dibandingkan dengan perlakuan lain. Peran CMA terhadap kesehatan tanaman telah banyak diteliti namun perannya dalam pengendalian penyakit yang menginfeksi daun masih dalam tahap penelitian dan menunjukkan hasil yang bervariasi (Gernns et al 2001), tanaman yang diinokulasi CMA cenderung lebih tahan terhadap patogen tipe nekrotrof (Fritz et al 2006;De La Noval et al 2007). Cendawan A. porri penyebab bercak ungu merupakan cendawan yang bersifat nekrotrofik, yaitu cendawan yang hidup dan berkembang pada sisa-sisa tanaman yang mati, dan apabila kondisi tanaman lemah, karena kekurangan unsur hara maupun cekaman lainnya maka dapat menyerang dan menimbulkan kerugian ekonomi (Woudenberg et al 2014).…”
Section: Pembahasanunclassified